Manajemen Mutu Terpadu dalam Pelaksanaan Link and Match 8+i SMK Pusat Keunggulan Sektor Hospitality di Daerah Istimewa Yogyakarta - Sulistyawati, Eko; Mulyono, Rahmat (Media Manajemen Pendidikan, 2024)
The purposes of this reseach are (1) to analyzed the facts contained in the information of total quality management at the Centre of Excellence Vocational School in the Special Region of Yogyakarta.; (2 to analyzed the facts contained in the information of link and match 8+i at the Centre of Excellence Vocational School in the Special Region of Yogyakarta; (3) to analyzed the facts contained in the information of link and match 8+i at the Centre of Excellence Vocational School in the Special Region of Yogyakarta. This type of research the author uses a qualitative approach. Data  collection techniques through in-depth interviews, observation, and documentation. Data analysis in this study used Miles and Huberman's model analysis. Researchers collect, reduce, present, and draw conclusions.   Based on the results of data analysis, it can be concluded that; (1) total  quality management at the SMK Center of Excellence for the hospitality sector in the Special Region of Yogyakarta has been implemented very well as demonstrated by the existence of strategic plans, quality policies, organizing, participatory leadership, ISO 9001: 2015 QMS systems and procedures, and has carried out self-assessments, which has been implemented in accordance with the quality guidelines that have been prepared and the applicable legislation and is supported by solid teamwork; (2) the link and match 8+i program at the Vocational High School Center of Excellence for the hospitality sector in the Special Region of Yogyakarta has been implemented even though not all of it has been maximized because it is still in the process until 2024, the link and match 8+i that has been implemented is a curriculum compiled together, project-based learning real world of work (PBL), the role of teachers/instructors from industry, apprenticeship or work practice in industry for at least 1 semester, competency certification according to standards and needs of the world of work for graduates and teachers, technology updates and training from industry, applied research supports teaching factory, commitment to absorption by the world of work, as well as (i) the possibility of other collaborations; (3) The role of integrated quality management in the implementation of link and match 8+i SMK Center of Excellence in the hospitality sector in the Special Region of Yogyakarta is very supportive so that the main objective of quality assurance in implementing link and match 8+i can be realized. The pillars of integrated quality management in schools can be seen from the focus on customers, total involvement, measurement, stakeholder commitment, and continuous improvement.